2009
DOI: 10.1007/s00253-009-1882-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioproducts from Aureobasidium pullulans, a biotechnologically important yeast

Abstract: It has been well documented that Aureobasidium pullulans is widely distributed in different environments. Different strains of A. pullulans can produce amylase, proteinase, lipase, cellulase, xylanase, mannanase, transferases, pullulan, siderophore, and single-cell protein, and the genes encoding proteinase, lipase, cellulase, xylanase, and siderophore have been cloned and characterized. Therefore, like Aspergillus spp., it is a biotechnologically important yeast that can be used in different fields. So it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
136
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(142 citation statements)
references
References 66 publications
2
136
0
4
Order By: Relevance
“…Till date most of the studies have been reported on mesophilic strain of this fungus which produces pullulan up to level of 30-36 g/l in flask shake experiments or in fermentor experiments at a temperature range of 24-32 o C at different physico-chemical conditions (4,7,8,9,11,13,15,17). However, a high yielding strain of A. pullulans has not been reported so far which can also sustain a high temperature above 35 o C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Till date most of the studies have been reported on mesophilic strain of this fungus which produces pullulan up to level of 30-36 g/l in flask shake experiments or in fermentor experiments at a temperature range of 24-32 o C at different physico-chemical conditions (4,7,8,9,11,13,15,17). However, a high yielding strain of A. pullulans has not been reported so far which can also sustain a high temperature above 35 o C.…”
Section: Introductionmentioning
confidence: 99%
“…The regular alternation of α-1, 4 and α-1, 6 bonds results in two distinctive properties that is structural flexibility and enhanced solubility (14). This polysaccharide is of great economic importance with increased applications in food, pharmaceutical, agricultural, blood plasma substitute and chemical industries (17,10,12). Pullulan produces a high viscosity solution at a relatively low concentration and can be used for oxygen-impermeable films and fibers, thickening or extending or adhesives or encapsulating agents (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, bands for A. pullulans were stronger from organic treatment samples. A. pullulans is a cosmopolitan yeastlike (black) fungus and is ubiquitously associated with plants, including grapevines (5,8). Cladosporium sp.…”
mentioning
confidence: 99%
“…Aureobasidium pullulans is popularly known as black yeast and widely distributed in the phyllosphere of many crop plants, on various tropical fruits, in fresh water, estuarine, marine sediments, hypersaline habitats, seawater and deep sea [20]. In this study, the mangrove swamp was proven to be another natural habitat that was suitable for A. pullulans though it was not the major species.…”
Section: Isolation and Routine Identification Of The Yeast Strainsmentioning
confidence: 83%